On a Family of Circle Homeomohphisms with One Break Point - Karshiboev Khayrullo Kilichovich (International Journal on Integrated Education, 2022)
this article, we study a one-parameter family of circle homeomorphisms with one break point. It is proved that in the case of a rational rotation number the number of periodic trajectories does not exceed two.